From fordist engineer to digital engineer: technological training UNI in 21st century Perú - Lima Fuentes, Noemí Guadalupe (2023)
When this article was titled, it to emphasize Fordism, this characteristic feature in engineers  training at National University Engineering (UNI), also contributed development´s years of engineering in the country. Mentioning “digital engineer” marks the important new technological paradigm in current academic training. This institution has managed to accredit 20 of its 23 engineering programs with ABET, prestigious worldwide accreditors. It is argued in this study that´s insufficient enough to guarantee this quality objective; because it is necessary to reflect first on demand for revolution  education technological, based on the observation of countries with best quality standards and best university-business-state relationship; that is interesting for relevant training engineers in the country of the 21st century.